Effects of Biosullary Application on Soil Fertility Status and Corn (Zea mays) Production after Two Planting Periods - Abdul Haris; Annas Boceng; Saida Saida; Abdul Akbar (AGRIVITA Journal of Agricultural Science, 2024)
Maize production in Indonesia faces challenges of climate change, affecting the deviation of planting seasons and overall yield stability. This study evaluates the impact of biosullary application on maize growth and yield across two planting periods using a Randomized Complete Block Design (RCBD). With twenty-one experimental units and treatments replicated three times, the study encompassed 252 plants and 63 sample plants. Findings indicate Treatment P6 consistently produced the tallest plants (199.67 cm), highest number of leaves (13.33 at planting period 1, 12.00 at planting period 2), and fastest flowering period (39.00 days at planting period 1, 45.00 days at planting period 2). P6 also showed notable cob length (11.67 cm in period 1), while Treatment P5 excelled in period 2 with 13.00 cm. Treatment P5 recorded the highest 100-seed weight (26.33 grams at planting period 1, 22.67 grams at planting period 2). To sustain maize productivity, increasing fertilizer dosage at the planting period 2 is recommended. Biosullary application not only enhances maize growth and yield but also improves soil physical properties, boosts microbial vitality, and stabilizes soil pH. These findings highlight biosullary potential as a sustainable approach to mitigate climate impacts and enhance maize production in Indonesia.